PESTISIDA PADA BUDIDAYA KEDELAI DI KABUPATEN BANTUL D. I. YOGYAKARTA - Arif Anshori; Catur Prasetiyono (Caraka Tani: Journal of Sustainable Agriculture, 2016)
Soybean farming carried out by farmer in Bantul Regency D.I. Yogyakarta. Pesticides still important in securing the soybean production of plant pests. Some farmers in the extreme assumes that pesticide with dose and high frequency can improve yields. The research was conducted in Bambanglipuro and Srandakan Bantul D.I. Yogyakarta on April to October 2012. The research aims to identify the use of pesticides in farming soybeans, soybean production and farmers income as well as pesticide residues in soybean dry seeds. Interviews were conducted with farmers, include the use of pesticides, soybean production and farmers income. Aside from interviews with farmers, pesticide usage data is also derived from used packaging were found at the site. Soybean dry seeds were taken from the site of the most intensive in the cultivation of soybeans and analyzed pesticide residues. The results showed that soybean farmers use pesticides in farming. Pesticides are used insecticides (69.6%), fungicides (17.4%), herbicides (8.7%) and other types (4.3%). Soybean yield 1,850 kg/ha, revenue Rp. 2.932.500,-/ha with B/C ratio 1.36. The active ingredient of pesticide residue organoposfat contained in the soybean dry seeds with concentration 0-0.068 mg/kg.